Early ward discharge clinic: facilitating discharges and prompt follow-up for medical inpatients in a district general hospital - Tasneem Ahmed; Georgia Kate Galloway; Sarah Nahin Choudhury (BMJ Open Quality)
Early discharge and follow-up for medical admissions could facilitate reduced length of stay and improve patient satisfaction. However, evidence to confirm this is lacking. Peterborough City Hospital (PCH) designed an early ward discharge clinic (EWDC) service embedded within its acute medicine department to provide clinicians with the opportunity for a prompt clinical review following a hospital admission.Across three cycles, several interventions aimed to improve the utilisation of clinic, appropriateness of referrals and reduce the number of missed attendances. Our work has demonstrated that a service such as the EWDC can provide ample opportunity for early review of patients which could reduce the rate of readmissions and improve services. Interventions to date have improved the utilisation of the clinic, reduced the number of patients not being aware of appointments and provided training opportunities for junior clinicians. Data has also suggested a high level of patient satisfaction from using the service.Further research is needed to confirm the use of such services in reducing readmissions and mortality, however, results from clinics at individual units such as PCH provide useful insight until such data is available.